Prisoners of Politics: Breaking the Cycle of Mass Incarceration - Barkow, Rachel E. (Harvard University Press, 2019)
Cover -- Title Page -- Copyright -- Dedication -- Contents -- Introduction -- Part One -- 1. Misleading Monikers -- 2. Senseless Sentencing -- 3. Counterproductive Confinement -- 4. Obsolete Outcomes -- 5. Collateral Calamities -- Part Two -- 6. Populist Politics -- 7. Institutional Intransigence -- Part Three -- 8. Policing Prosecutors -- 9. Engaging Experts -- 10. Catalyzing Courts -- Conclusion -- Notes -- Acknowledgments -- Index